Longer Lag Time in Early-Stage Retinoblastoma - Citra, Anindya; Utomo, Budi; Soebagjo, Hendrian Dwikoloso (Folia Medica Indonesiana, 2022)
Highlights: • Patients with IRSS I stage have the longest lag time than IVB stage. • Lag time is no significant with stage retinoblastoma. Abstract: Retinoblastoma is a rare neoplasm disease that occurs in children, generally under the age of two. Retinoblastoma is more prevalent in developing countries and is often associated with a late diagnosis. Such delays can lead to a poor prognosis. The time from the appearance of symptoms of retinoblastoma (onset) to the time of diagnosis is called lag time. Early diagnosis of retinoblastoma by paying attention to factors such as age, clinical symptoms, and laterality can help improve retinoblastoma survival rates, especially in developing countries. The purpose of this study was to analyze the relationship between the lag time to the stage of retinoblastoma patients at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. This study was a retrospective analytical observational study using secondary data from retinoblastoma patients at the Ophthalmology Outpatient Unit at Dr. Soetomo General Academic Hospital, Surabaya, from January 2014 to December 2018. The data were analyzed using Kendall's tau-C test. No significant correlation was found between lag time and stage (p = 0.339). Patients with International Retinoblastoma Staging System (IRSS) I stage had the longest lag time (on average 28 months), and patients with stage IVB had the shortest lag time (on average four months). There was no correlation between lag time and retinoblastoma stage. However, there was a trend of patients with early stages delaying hospital visits, while patients with advanced stages in earlier to the hospital.